1985
DOI: 10.1177/156482658500700308
|View full text |Cite
|
Sign up to set email alerts
|

Urban Agriculture: Who Cultivates and why? a Case-Study of Lusaka, Zambia

Abstract: Contrary to the official view that rejects urban cultivation as an irrational activity by a small group of recent migrants who have yet to be integrated into the urban environment, urban agriculture is an innovative response by a majority of the urban poor, who are fully entrenched in an urban economy that currently lacks the capacity to provide them with sufficient real income. Though insufficient income is a primary reason, it is not the only factor affecting a household's decisions regarding cultivation. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 3 publications
1
28
1
1
Order By: Relevance
“…Home gardens are an essential part of household agro- systems in the tropics, and they show a wide variety of management practices (Wiersum 1982;Niñez 1985b;Torquebiau 1992). These have been shown to reflect socioeconomic conditions, productive orientations, global family strategies and ecological conditions (Wiersum 1982;Sanyal 1985;MacDicken 1990;Méndez et al 2001;González Jácome 2003;Shajaat Ali 2005).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Home gardens are an essential part of household agro- systems in the tropics, and they show a wide variety of management practices (Wiersum 1982;Niñez 1985b;Torquebiau 1992). These have been shown to reflect socioeconomic conditions, productive orientations, global family strategies and ecological conditions (Wiersum 1982;Sanyal 1985;MacDicken 1990;Méndez et al 2001;González Jácome 2003;Shajaat Ali 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, because HSA gardens are more productive both strategies sold similar amounts of energy, although the amount sold may have represented important cash differences that favor HCA households. The emphasis on animal production for the market has also been observed amongst rural colonists of urban origin in the tropical forests of Colombia (Pinton 1985;Sanyal 1985). In Calakmul, all HSA migrants came from agricultural households in their home towns, but many HCA migrants came from urban areas (Rodríguez 2003).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Two studies showed that the majority of participants practiced UA both to provide food for the household and to generate income (Asomani-Boateng, 2002;Adeoti and Egwudike, 2003). In some cases, the lines were blurred between motivations of subsistence and income-generation, as participants reported the unaffordable cost of food or the need to minimize food expenses as motivations (Sanyal, 1985;Gbadegesin, 1991;Flynn, 2001). Across included studies, only one (Ngome and Foeken, 2012) found that a small minority of participants reported reasons aside from subsistence or income-generation for practicing UA (e.g., gardening as a hobby).…”
Section: Why Individuals Engage In Ua: Motivationsmentioning
confidence: 86%
“…The remaining 12 studies included both farmers and non-farmers: nine sampled cases from the general population within specified cities (Sanyal, 1985;Memon and Lee-Smith, 1993;Maxwell, 1995;Gockowski et al, 2003;Hovorka, 2006;Foeken and Owuor, 2008;Hillbruner and Egan, 2008;Crush et al, 2011;Gallaher et al, 2013), two used data from national surveys representing the general population (Ersado, 2005;Zezza and Tasciotti, 2010), and one study recruited a comparison group of non-farmers . Two studies made multi-country comparisons: Zezza and Tasciotti (2010) used nationally representative data from 15 countries across several continents, and Crush et al (2011) compared data from poor urban neighborhoods in 11 southern African cities representing nine countries.…”
Section: Participantsmentioning
confidence: 99%